ANTIHYPERGLICEMIA ACTIVITY OF WATER FRACTION, ETHYL ACETATE FRACTION, AND N- HEXANE FRACTION OF SPINACH LEAVES EXTRACT (Amaranthus Cruentus L) ON MALE MICE SWISS - Nofianti, Tita (JURNAL FARMASI GALENIKA, 2015)
The activity test ofthe water fraction, ethyl acetate and n-hexane fraction of spinach leaves (Amaranthus cruentus L) has been conducted using the glucose tolerance method on male mice Swiss webster strain. The dose were water fraction 0.086 g/kg bw, ethyl acetate fraction 0.03g/kg body weight and n-hexane fraction 0.055 g/kg bw. Time measurement of blood glucose levels was conducted every 30 minutes for 120 minutes using a glucometer. The results showed that administration of water fraction, ethyl acetate fraction and n-hexane fraction of spinach leaves can lowering the blood glucose level of white male mice. While the best group that lowering the blood glucose level was ethyl acetate fraction 0,03 g/kg bw when compared to water fraction and n-hexane fraction. It can be concluded that spinach leaves showed antihyperglicemia.